2016
DOI: 10.1021/acs.jproteome.6b00629
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Biomarkers for Tasmanian Devil Cancer (DFTD) by Metabolic Profiling of Serum

Abstract: Devil facial tumor disease (DFTD) is a transmissible cancer threatening Tasmanian devils (Sarcophilus harrisii) with extinction. There is no preclinical test available for DFTD, and thus our aim was to find biomarkers for DFTD by metabolic fingerprinting. Seventy serum samples from wild Tasmanian devils (35 controls, 35 with tumors) were analyzed by liquid chromatography-high-resolution mass spectrometry. Features were selected by multivariate models (PLS/DA, random forests) comparing age-matched training set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This devastating disease is spread among devils via biting during social interactions 35 . The devil’s immune system is unable to mount an effective immune response to the tumour as DFTD cells are able to avoid immune recognition by down-regulating MHC expression 36 , 37 . Metabolic failure, tumour related cachexia and metastases result in devil death within 6 to 9 months of the emergence of the first lesions 38 .…”
Section: Introductionmentioning
confidence: 99%
“…This devastating disease is spread among devils via biting during social interactions 35 . The devil’s immune system is unable to mount an effective immune response to the tumour as DFTD cells are able to avoid immune recognition by down-regulating MHC expression 36 , 37 . Metabolic failure, tumour related cachexia and metastases result in devil death within 6 to 9 months of the emergence of the first lesions 38 .…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to identify DFTD serum biomarkers that could potentially serve to predict preclinical stages, Karu et al. ( 24 ) demonstrated that a panel of fibrinogen peptides and seven metabolites could differentiate devils with overt DFTD from healthy controls with high sensitivity and specificity. Another study found elevated levels of the receptor tyrosine-protein kinase ERBB3 in the serum of devils infected with DFTD compared to healthy controls ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…McCallum et al (McCallum et al, 2009) suggested that the disease is unlikely to spread between individuals prior to the development of clinical signs, however this assumption has not been validated due to the lack of a preclinical test. In an effort to identify DFTD serum biomarkers that could potentially serve to predict preclinical stages, Kau et al (Karu et al, 2016) demonstrated that a panel of fibrinogen peptides and seven metabolites could differentiate devils with overt DFTD from healthy controls with high sensitivity and specificity. Another study found elevated levels of the receptor tyrosine-protein kinase ERBB3 in the serum of devils infected with DFTD compared to healthy controls (Hayes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%